2013
DOI: 10.2217/whe.13.30
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Interventions Serving US-Based Latinas: Current Approaches and Directions

Abstract: Despite efforts to reduce morbidity and mortality in breast cancer, Latinas continue to have lower 5-year survival rates than their non-Latina white counterparts. All along the cancer continuum from screening to follow-up of abnormal screening to diagnosis and treatment to survivorship, Latinas fare poorer than non-Latina whites. To close this gap, a number of research projects across the continuum have attempted to improve breast cancer outcomes. In this review, we examine studies that have been carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 84 publications
(120 reference statements)
0
60
0
Order By: Relevance
“…Latina patients with breast cancer and survivors appear to have lower quality of life, including poorer emotional and social functioning, compared to NLC counterparts (Bickell et al, 2006; Fedewa, Ward, Stewart, & Edge, 2010). A large body of literature exists that has characterized and addressed modifiable factors associated with early detection of breast cancer, including promotion of mammography screening among Latinas (Guerra, Krumholz, & Shea, 2005; Molina, Thompson, Espinoza, & Ceballos, 2013; Purc-Stephenson & Gorey, 2008; Santiago-Rivera, Arrendondo, & Gallardo-Cooper, 2002). However, little research exists to date of quantified ethnic differences in mental health comorbidities after abnormal screening results.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Latina patients with breast cancer and survivors appear to have lower quality of life, including poorer emotional and social functioning, compared to NLC counterparts (Bickell et al, 2006; Fedewa, Ward, Stewart, & Edge, 2010). A large body of literature exists that has characterized and addressed modifiable factors associated with early detection of breast cancer, including promotion of mammography screening among Latinas (Guerra, Krumholz, & Shea, 2005; Molina, Thompson, Espinoza, & Ceballos, 2013; Purc-Stephenson & Gorey, 2008; Santiago-Rivera, Arrendondo, & Gallardo-Cooper, 2002). However, little research exists to date of quantified ethnic differences in mental health comorbidities after abnormal screening results.…”
mentioning
confidence: 99%
“…Most research has focused on predominantly NLC women or has not addressed racial or ethnic differences (Andrés-Hyman, Ortiz, Añez, Paris, & Davidson, 2006; Molina et al, 2013). Although the authors of the current article found no study that compared distress among Latinas and NLC women, one qualitative study with a largely Latina sample noted that psycho logical distress interfered with motivation to schedule a follow-up appointment (Allen, Shelton, Harden, & Goldman, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The past decade has seen an increase in observational research focusing on the HRQoL of women diagnosed with breast cancer, including Hispanic women, [1217] as well as a handful of studies documenting the efficacy of supportive interventions to improve HRQoL among Hispanic women diagnosed with cancer [13,16]. While preliminary findings suggest that increasing cancer knowledge, self-efficacy in communication, and self-management skills can improve HRQoL outcomes in this population [6,1722], the extant literature is limited by in-person or phone-based treatment modalities.…”
Section: Introductionmentioning
confidence: 99%